2017
DOI: 10.21082/jpasca.v13n1.2016.28-35
|View full text |Cite
|
Sign up to set email alerts
|

Characterics of Freeze Dried Jack Bean Yogurt Powder with Maltodextrin as Coating Material

Abstract: <p>Jack bean has the potential to be developed as food products. One of them is yogurt, but the shelf life of yogurt is short. The attempt to increase the shelflife of yogurt is making yogurt powder using freeze drying by adding maltodextrin as coating material. This study aims to determine the exact concentration of maltodextrin in order to produce jack bean yogurt powder with good characteristics and organoleptic characteristics that prefer by panelists. This study using experimental method with random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
(9 reference statements)
0
1
0
1
Order By: Relevance
“…Djali, Indiarto, and Avila [13] added that adding maltodextrin from 5-30% significantly reduced the total titratable acid to 0.31% in sword bean powdered yoghurt. Djali, Marta, and Harnah [14] reported that adding a maltodextrin concentration of up to 30% significantly reduced the total titratable acid to 0.56% in soybean powdered yoghurt.…”
Section: Dmentioning
confidence: 99%
“…Djali, Indiarto, and Avila [13] added that adding maltodextrin from 5-30% significantly reduced the total titratable acid to 0.31% in sword bean powdered yoghurt. Djali, Marta, and Harnah [14] reported that adding a maltodextrin concentration of up to 30% significantly reduced the total titratable acid to 0.56% in soybean powdered yoghurt.…”
Section: Dmentioning
confidence: 99%
“…Total asam tertitrasi yogurt bubuk menunjukkan hubungan yang berbanding terbalik dengan pH. Djali et al, (2016) melaporkan bahwa penambahan maltodekstrin dari 5-30% signifikan terhadap penurunan total asam tertitrasi sampai 0,31% dari yoghurt bubuk kacang roro pedang. Djali et al, (2017) melaporkan bahwa penambahan konsentrasi maltodekstrin dari sampai 30% signifikan menurunkan total asam tertitrasi sampai 0,56% dari soygurt bubuk kacang kedelai.…”
Section: Total Asam (%)unclassified